2018
DOI: 10.5539/mas.v12n5p60
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Intended Learning Outcomes and Learning Activities of Action Pack Textbooks in Jordan

Abstract: This study aims to analyze the intended learning outcomes (ILOs) and learning activities in Action Pack textbooks for Jordan in light of the EFL curriculum objectives. in Jordan (delete "in Jordan", because it is redundant). The sample of the study consisted of Action Pack textbooks for three grade levels students ( delete "students" because it does not seem necessary to the meaning of the sentence) (grade 6, 10, 12) during the academic year 2014/2015. A specially prepared coding sheet was developed by the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The five-point Likert scale was used to measure the variables, and mean value and standard deviation were used to reflect the level of variables. Omari (2018) suggested that the mean values in different ranges represented corresponding levels (high, moderate and low), which was shown in Table 2. As demonstrated in the Table 3, the mean scores for students' perceived parental expectations (SPPE), academic self-efficacy (ASE), and academic engagement (AE) are 3.62, 3.51 and 3.54.…”
Section: Descriptive Statisticsmentioning
confidence: 90%
“…The five-point Likert scale was used to measure the variables, and mean value and standard deviation were used to reflect the level of variables. Omari (2018) suggested that the mean values in different ranges represented corresponding levels (high, moderate and low), which was shown in Table 2. As demonstrated in the Table 3, the mean scores for students' perceived parental expectations (SPPE), academic self-efficacy (ASE), and academic engagement (AE) are 3.62, 3.51 and 3.54.…”
Section: Descriptive Statisticsmentioning
confidence: 90%
“…On the other hand, English language teachers may develop classroom activities that cater for different types of intelligence and learning styles. They can also assume different roles such as facilitators, observers, curriculum developers, lesson designers and analysts (Botelho 2003;Currie 2003;Omari 2018). Arnold andFonseca (2004, as cited in Spirovska 2013, 6) stated, "With MIT applied in the language classroom, teachers are better able to tap into the areas of personal meaningfulness of their students since they are recognizing the differences inherent in the students and putting individuals with their different ways of learning where they belong, back at the Centre of the learning process."…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…There are distinguishing characteristics of effective learning outcomes (Omari, 2018). Learners must master a corpus of fundamental information across all disciplines to succeed and, therefore, a whole set of applications in which they can use that knowledge (Mallidou, Atherton, Chan, Frisch, Glegg, Scarrow, 2018).…”
Section: Introductionmentioning
confidence: 99%